2023
DOI: 10.3389/fdata.2022.997447
|View full text |Cite
|
Sign up to set email alerts
|

Flood risk assessment for residences at the neighborhood scale by owner/occupant type and first-floor height

Abstract: Evaluating flood risk is an essential component of understanding and increasing community resilience. A robust approach for quantifying flood risk in terms of average annual loss (AAL) in dollars across multiple homes is needed to provide valuable information for stakeholder decision-making. This research develops a computational framework to evaluate AAL at the neighborhood level by owner/occupant type (i.e., homeowner, landlord, and tenant) for increasing first-floor height (FFH). The AAL values were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…The calculation begins by utilizing the computational framework developed by Al Assi et al (2023) for determining the annual flood risk, considering both home attributes and flood data. The framework developed by Al Assi et al (2023) was chosen because it offers several advantages for the analysis of AAL across multiple homes. First, it utilizes a refined numerical integration method that allows for a more mathematically elegant calculation of AAL.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The calculation begins by utilizing the computational framework developed by Al Assi et al (2023) for determining the annual flood risk, considering both home attributes and flood data. The framework developed by Al Assi et al (2023) was chosen because it offers several advantages for the analysis of AAL across multiple homes. First, it utilizes a refined numerical integration method that allows for a more mathematically elegant calculation of AAL.…”
Section: Methodsmentioning
confidence: 99%
“…Third, the damage initiation point according to the selected DDF affects risk assessment. For example, Al Assi et al (2023) showed that considering the damage initiation point at depths less than zero increases the AAL substantially. Therefore, future research should focus on the accuracy of the flood maps, DDFs, and the damage initiation point.…”
Section: Present Value Of Annual Flood Risk and Flood Risk Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Flood risk is assessed as the product of flood occurrence probability and the associated consequences (Šugareková & Zeleňáková, 2021). Average annual loss (AAL) has been used in past research to represent flood risk (Hallegatte et al, 2013;Armal et al, 2020;Rahim et al, 2021;Mostafiz et al, 2022a;Bowers et al, 2022;Wing et al, 2022;Yildirim & Demir, 2022;Al Assi et al, 2023b;Friedland et al, 2023) in terms of costs associated with direct building loss, direct contents loss, and indirect losses such as use loss while the building is being renovated (Al Assi et al, 2023a). AAL is calculated as the integral of flood loss as a known function of the flood probability (or flood return period), and the Gumbel distribution function is one of the most widely accepted probability functions (Singh et al, 2018;Patel, 2020).…”
Section: Introductionmentioning
confidence: 99%